Experimental investigation on the performance of a pyramid solar still for varying water depth, contaminated water temperature, and addition of circular fins - Yuvaperiyasamy, Mayilsamy; Senthilkumar, Natarajan; Deepanraj, Balakrishnan (International Journal of Renewable Energy Development, 2023)
The experimental investigation was meant to investigate the effect of water depth in the basin, the water temperature at the inlet of solar still, and adding circular fins to the pyramid solar still on freshwater output. The investigation was divided into three sections. The first area of research is to study effect of increasing water depth in the solar still, which ranged from 2 to 6 cm, second section concentrated on varying the inflow water temperature from 30 to 50ºC, and third section investigated the influence of incorporating circular fins into the solar still basin on the water output and quality. The experimental findings showed that basin depth considerably impacts freshwater flow. The highest significant difference, 38%, was recorded by changing the water level in the basin from 2 to 6 cm. Freshwater yielded the most at a depth of 2 cm, totalling 1250.3 mL, followed by 1046 mL at a depth of 3 cm. A water depth of 4 cm produced 999 mL, whereas a water depth of 5 cm made 911 mL. The lowest production occurred at a water depth of 6 cm, producing 732 mL; furthermore, including fins at the bottom increased productivity by 8.2%. Elevating the temperature from 30 to 50ºC of the inlet water led to a water output increase of 15.3% to 22.2%. These findings underscore the profound potential of harnessing solar energy to address global water challenges and pave the way for further advancements in efficient freshwater production